Recyclable Nanoporous Materials with Ordered Tunnels Self‐Assembled from α‐ and γ‐Cyclodextrins. Issue 6 (13th May 2019) - Li, Qingxuan; Wang, Jin; Ye, Lin; Zhang, Aiying; Zhang, Xuetong; Feng, Zengguo
Abstract: A straightforward method to create nanoporous materials via the self‐assembly of macrocyclic molecules (MCMs) is proposed and fulfilled by using cyclodextrins (CD) as building blocks. Due to molecular geometry, α‐CD forms a hexagonal nanoporous crystal, whereas γ‐CD forms a cuboid crystal. The resulting products are confirmed by FTIR, 1 H NMR and solid‐state 13 C NMR to be solely built up by CDs. Well‐defined and monodisperse nano‐tunnels are formed in nanoporous materials by the template‐free, face‐to‐face self‐assembly of CDs, with diameters around 0.8 or 0.5 nm equal to the diameter of the CD cavities. Moreover, the nanoporous structure of the CD is reversible controlled simply by switching temperature in DMF, indicating that the nanoporous CDs could be recyclable used and recovered. These characteristic properties and behaviors of the nanoporous CDs made them to be an ideal green material for absorption, separation as well as CD recovery. Abstract : The guest‐free self‐assembly of α‐ and γ‐CD in DMF can lead to lower critical solution temperature behavior where nanoporous crystals with monodisperse nano‐tunnel are produced. The nanoporous crystals can absorb 4‐bromide‐nitrobenzen by CD's inclusion property. It was further found that the formation procedure of nanoporous CD materials can also be used to recover CD from its inclusion complex. Consequently, nanoporous CD crystals show potential to be ideal green materials for absorption and separation, as well as CD recovery.